1994
DOI: 10.1287/mnsc.40.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Explorations of Negotiation Behaviors in Ten Foreign Cultures Using a Model Developed in the United States

Abstract: The universality of a problem-solving model of business negotiations is explored using 700 business people from 11 cultures as participants in a bargaining simulation. Both theoretical and measurement issues are considered using structural equations and partial least squares as the primary data analysis approaches. The results regarding the universality question are equivocal---findings varied across cultural groups in most cases. However, the theoretical model still appears to be a useful tool for understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
187
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(195 citation statements)
references
References 71 publications
(85 reference statements)
5
187
0
3
Order By: Relevance
“…Another example of comparing cultures without cross-cultural interaction used 700 business people from the United States, Canada (both Anglophone and Francophone), Mexico, United Kingdom, France, Germany, Union of Soviet Socialist Republics, Taiwan, China, and Korea (Graham, Mintu, & Rodgers, 1994). Participant pairs attempted to increase joint profit in 30 minutes, and results suggests the degree to which both negotiators and partners utilized problem-solving approaches that impacted joint profit across cultural groups.…”
Section: Influence Attempts In Different Culturesmentioning
confidence: 99%
“…Another example of comparing cultures without cross-cultural interaction used 700 business people from the United States, Canada (both Anglophone and Francophone), Mexico, United Kingdom, France, Germany, Union of Soviet Socialist Republics, Taiwan, China, and Korea (Graham, Mintu, & Rodgers, 1994). Participant pairs attempted to increase joint profit in 30 minutes, and results suggests the degree to which both negotiators and partners utilized problem-solving approaches that impacted joint profit across cultural groups.…”
Section: Influence Attempts In Different Culturesmentioning
confidence: 99%
“…Although PLS (partial least squares) is a powerful tool in dealing with small samples (Graham et al 1994), a larger sample would allow for more variations in terms of splitting the data. A further limitation is that some of the fi rms that qualifi ed as born globals are already past their start-up phase.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Strategic alliances and multilateral negotiations have become essential to successful international relations. When conducting international business (Graham, Mintu and Rodgers 1994). Gulbro and Herbig (1998) indicated that for achieving successful agreements, negotiations are important in order to eliminate conflicting points of view between the representatives.…”
Section: Review Of the Literaturementioning
confidence: 99%